Modelos de dispersão populacional do muriqui-do-norte, Brachyteles hypoxanthus (Primates, Atelidae) - Santos, Bruna Silva (2012)
The northern muriqui, Brachyteles hypoxanthus (Primates: Atelidae) is endemic to the Brazilian Atlantic Forest and lives in groups of several males and females, in which males are filopatrics and females disperse from their natal groups before becoming active sexually. The original vegetation of the study area, in the municipality of Santa Maria de Jetibá (SMJ), has been replaced for different types of land use and land cover causing the fragmentation and loss of habitats. This research aimed to simulate the dispersion of five groups of northern muriqui, estimate the number of individuals and the area occupied in the future, identify key areas for dispersion and propose ecological corridors to enable the formation of metapopulation. We used data collected during the years 2002 to 2011. In 2011 there were 75 northern muriqui living in the fragments studied. The five groups showed positive population growth, and the average rate of population growth of the five groups was 4.97% per year and the average population density of 0.11 ind./ha. We created models of population growth, demand of area, and muriqui dispersion, considering the need to increase the area to support the growing number of animals, assuming that the muriquis will need to migrate to new forest fragments when they reach the carrying capacity of the fragment. We generated maps using the best paths for dispersion and also the fragments that are more likely for them to disperse first. Using the path in the map for dispersal of muriquis we formulated a map of ecological corridors linking patches of medium and advanced secondary forest among the five forest fragments containing muriquis. The results showed it is required 1.432 meters of forest corridors with a total area of 7.2 ha.The fragmentation and isolation of forest fragments hampers muriquis migration and dispersal of females during the breeding season, thus causing decreasing in population growth. The population growth of the species is also limited by the availability of suitable areas for occupation and the landscape matrix transpose. Knowing which fragments have higher probability of occupation by muriquis and which can be connected are important for formation of metapopulation, dispersal of females at reproductive age and colonization of new fragments. Thus, modeling the dispersal of muriquis, its population growth, and area is important since it is a new tool to support decisions about species conservation and restoration of forests